Citizen coproduction and social media communication: Delivering a municipal government's urban services through digital participation - Wonhyuk Cho; Winda Dwi Melisa (Administrative Sciences, 2021)
This study investigated how social media is used by a municipal government agency for communication of citizen coproduction initiatives, through social media content analysis of the government's official Twitter account. This article identified that the dominant form of social media coproduction in the Bandung municipal government in Indonesia is government-to-citizen (G2C) interaction, focused primarily on informing and nudging (86.62%) citizens, as well as some limited elements of citizen-to-government (C2G) communication, such as citizen sourcing and citizen reporting (8.96%). The municipal government uses various visual tools on Twitter to disseminate G2C information and convey its messages. Regarding the phase of the service cycle, this study found that the majority of social media communications are related to co-assessment (52.26%) and co-designing (42.24%), with a limited number of tweets about co-delivery (3.25%). Based on these findings, this article discusses the shifting relationship between government and citizens brought on by the adoption of this social media platform in its service delivery arrangement.
Keywords: 350; coproduction; local government; public service; social media; twitter